ANALISIS PERBANDINGAN DAYA HAMBAT EKSTRAK PIROLISIS DAN EKSTRAK MASERASI DAUN TEMBAKAU (Nicotiana tabacum L.) VAR. VIRGINIA TERHADAP Trichophyton rubrum SECARA IN VITRO - Ollsya Adhina Riezqia Harahap (2023)
The prevalence of onychomycosis globally increases with the main etiology Trichophyton rubrum. Effective management for onychomycosis is still a challenge because it can cause side effects and recurrence so that alternative tobacco leaf treatment is carried out. Tobacco leaves have antifungal components that are able to decrease fungi's growth. Extraction methods for obtaining tobacco extract include pyrolysis and maceration methods. The goal of this study is to analyze the comparison of inhibitory power of pyrolysis extraction and maceration of tobacco leaves as an antifungal in the growth of Trichophyton rubrum in vitro. The ingredients used in the study were pyrolysis extract and tobacco leaf maceration extract with concentrations of 20%, 40%, 60%, 80%, and 100%. The antifungal test used is the well diffusion method. The results showed that pyrolysis extract and maceration extract have an effect as antifungals. Mann Whitney's statistical results obtained a p value of <0.05 that there was a significant difference between the treatment group of pyrolysis extract and maceration extract in inhibiting Trichophyton rubrum. Pyrolysis extract is more effective in inhibiting Trichophyton rubrum than maceration extract with a wider inhibition zone diameter at the same group of concentration because the pyrolysis method is able to extract more secondary metabolite components through heating. Pyrolysis extract at a concentration of 40% with an inhibitory zone diameter of 10.85 mm is the most effective concentration with strong inhibitory power in inhibiting Trichophyton rubrum, while tobacco leaf maceration extract is concentration of 80% with an inhibition zone diameter of 11.52 mm. The quantitative test results showed that pyrolysis extract and maceration contain the same secondary metabolites, but with quantitative tests pyrolysis extract contains higher levels than maceration extract. Keywords: Antifungal, Maceration, Pyrolysis, Tobacco Leaf, Trichophyton rubrum